2009
DOI: 10.1007/s11832-009-0175-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of late-onset Perthes’ disease using four different treatment modalities

Abstract: Purpose The outcome of Perthes' disease in children over 8 years tends to be poor. It is unclear whether any treatment modality alters the natural history. This study compares the results of four treatment modalities for this group of patients. Methods A retrospective review was performed of prospectively collected data for 44 children (48 hips) with Catterall grade 2, 3 or 4 Perthes' disease with onset age 8 years or older followed to maturity. Patients were divided into four groups (a no-treatment group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
0
21
0
1
Order By: Relevance
“…Instead, recent research tends to focus on treatment modalities (Kim, ). Treatment methods vary from observation to immobilization, splintage, or surgery depending on the child's age, the level of damage experienced by the bony epiphysis, and the beliefs of the surgeon (Catterall, ; Stulberg et al, ; Herring et al, ; McQuade and Houghton, ; Canavese and Dimeglio, ; Osman et al, ). Past treatment methods focused on immobilization and reduction of the loading of the hip in the hope that this would prevent further collapse of the femoral head (Danforth, ; Herndon and Heyman, ; Goff, ; Katz, ).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, recent research tends to focus on treatment modalities (Kim, ). Treatment methods vary from observation to immobilization, splintage, or surgery depending on the child's age, the level of damage experienced by the bony epiphysis, and the beliefs of the surgeon (Catterall, ; Stulberg et al, ; Herring et al, ; McQuade and Houghton, ; Canavese and Dimeglio, ; Osman et al, ). Past treatment methods focused on immobilization and reduction of the loading of the hip in the hope that this would prevent further collapse of the femoral head (Danforth, ; Herndon and Heyman, ; Goff, ; Katz, ).…”
Section: Introductionmentioning
confidence: 99%
“…This may be accomplished by shelf acetabuloplasty, a varus osteotomy or abduction plasters. 24 In our short series of 3 patients with the mean CE angle of 13.67 0 ±4.04 0 , two patients in the age group of 5-8 years, of which one had CE angle of 18 0 and a well contained head, was treated by abduction plasters, and other one had CE angle of 10 0 , so for head containment varus osteotomy procedure had been done. One patient was of adolescent age group and on subsequent follow-up his CE angle reduced to 13 0 so the operative treatment in the form of varus osteotomy was performed.…”
Section: Discussionmentioning
confidence: 83%
“…13 Several surgical procedures have been offered but no treatment has been shown convincingly to be significantly effective in improving the outcome of Perthes' disease or of influencing its course. 3 Osman et al 2 showed, in their retrospective review, poor outcomes of treatment in LCPD with increasing age. Contrary to this, hip distraction has been shown to be valuable in certain cases of LCPD that have poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These patients are those in whom the disease presents at an advanced stage (mainly Herring's lateral pillar type C) after the age of 8 years. 2 Late-presenting cases form around 20% of all cases of LCPD. 3 Generally, they have poor outcomes.…”
Section: Introductionmentioning
confidence: 99%